AndroEvolve: Automated update for Android deprecated-API usages - HARYONO, Stefanus A. (Institutional Knowledge at Singapore Management University, 2021)
The Android operating system (OS) is often updated, where each new version may involve API deprecation. Usages of deprecated APIs in Android apps need to be updated to ensure the apps' compatibility with the old and new versions of the Android OS. In this work, we propose AndroEvolve, an automated tool to update usages of deprecated Android APIs, that addresses the limitations of the state-of-the-art tool, CocciEvolve. AndroEvolve utilizes data flow analysis to solve the problem of out-of-method-boundary variables, and variable denormalization to remove the temporary variables introduced by CocciEvolve. We evaluated the accuracy of AndroEvolve using a dataset of 360 target files and 20 deprecated Android APIs, where AndroEvolve is able to produce 319 correct updates, compared to CocciEvolve which only produces 249 correct updates. We also evaluated the readability of AndroEvolve's update results using a manual and an automatic evaluation. Both evaluations demonstrated that the code produced by AndroEvolve has higher readability than CocciEvolve's. A video demonstration of AndroEvolve is available at https://youtu.be/siU0tuMITXI.